PLANNING OF ECOLOGICAL AGRICULTURAL TOURIST ATTRACTIONS BASED ON THE CONCEPT OF CIRCULAR ECONOMY (Conferencea, 2023)
With the continuous development of society and the continuous improvement of people's living standards, leisure agricultural tourism based on agricultural production has gradually become popular, which takes agricultural landscape, agricultural experience and agricultural product shopping as content, and leisure agricultural tourist attractions have emerged. At present, some ecological agriculture projects are reconstruction or transformation projects, which are the recreational transformation of the original base for traditional agricultural projects in order to survive and seek market stimulation. However, due to the unscientific planning of the basic system, the low level of operation and management, and the lack of a scientific theoretical system for demonstration during the transformation process, the planning and transformation of the ecological agriculture project have not been promoted, and the project industry development has not been improved. Therefore, under the support of the concept of circular economy, this paper combines the Internet of Things technology to carry out the planning and analysis of ecological agricultural tourist attractions, and combines the experiments to analyse the effectiveness of this method. From the research point of view, it can be known that the ecological agricultural scenic area planning method constructed in this paper has certain effects.